Characteristics of Economic Potential and Spatial Development Differentiation of Rural Communes in Lubelskie Voivodship - Pomianek, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The paper presents characteristics of the economic potential of territorial units at LAU-2 level. The analysis included 170 rural communes in Lubelskie Voivodship. Based on eight variables, Hellwig’s taxonomic meter enabled grouping the communes according to their level of economic development. 29 of them were distinguished as relatively highly developed, whereas 22 communes represented a low level of development. Units with high level of development were distributed mainly in following districts: Bialski, Lubelski, Lukowski and Leczynski. The weakest communes were focused in Janowski, Zamojski and Lubelski districts. It may be noted that the geographical location of rural communes in lubelski district has a significant influence on their differentiation and development. The communes surrounding the capital of the province – Lublin – represented the group of high development level, while communes located peripherally were qualified to the weakest group.